Pengaruh Gamifikasi, dan Pengalaman Pelanggan terhadap Loyalitas Pelanggan Generasi Z pada Penggunaan Aplikasi Shopee - Abaharis, Henryanto; Rahma, Aulia (Lembaga Yasin AlSys, 2026)
Although the rapid growth of e-commerce has received attention in various studies, research that specifically discusses the effect of gamification and customer experience on Generation Z customer loyalty in the Shopee application remains limited. This study aims to analyze the effect of gamification and customer experience on the loyalty of Generation Z customers who use the Shopee application. This study used a quantitative approach with a survey design, involving 120 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with the assistance of SPSS. The results show that gamification and customer experience have a positive and significant effect on customer loyalty, both partially and simultaneously. This finding contributes to the development of customer loyalty theory in the context of digital marketing and broadens understanding of Generation Z consumer behavior on e-commerce platforms. The conclusion of this study emphasizes that interactive gamification-based features and positive digital experiences play an important role in increasing customer loyalty. The implications of this study include theoretical contributions to the digital marketing literature and practical recommendations for e-commerce industry players, particularly Shopee, in designing customer retention strategies through gamification innovation and improving the quality of user experience.